2006
DOI: 10.1039/b610601c
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 hierarchical hollow cubic cages assembled by bilayers: one-step synthesis and their electrochemical hydrogen storage properties

Abstract: Micrometer scaled MoS2 hierarchical hollow cubic cages assembled by bilayers can be synthesized via a one-step self-assembly coupled with intermediate crystal templating process without any surfactant, in which the intermediate K2NaMoO3F3 crystal formed in-situ and then served as the self-sacrificed template based on the Kirkendall Effect; The MoS2 hierarchical hollow cubic cages were employed for electrochemical hydrogen storage with a high capacity of 375 mAh g(-1) due to the more active edges exposing on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
92
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 32 publications
3
92
0
Order By: Relevance
“…Many reports have involved the application of MoS2 in lithium-ion batteries, since lithium ions can intercalate between the layers. [30][31][32] Remarkably, expanded MoS2, fabricated via lithiation method with an enlarged c lattice parameter, has achieved higher capacity with longer cycling span than commercial MoS2 (C-MoS2). The expanded MoS2 tends to be prone to serious restacking, however, due to its high surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have involved the application of MoS2 in lithium-ion batteries, since lithium ions can intercalate between the layers. [30][31][32] Remarkably, expanded MoS2, fabricated via lithiation method with an enlarged c lattice parameter, has achieved higher capacity with longer cycling span than commercial MoS2 (C-MoS2). The expanded MoS2 tends to be prone to serious restacking, however, due to its high surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In this context, layered mesoporous birnessite-type manganese oxide materials are attracting great interest due to their high surface area, low density, and good permeation. [13][14][15][16][17] However, the fabrication of birnessite-type manganese oxide architectures remains a significant challenge due to the fast and uncontrolled growth process. 18,19 Literature reviews of electrodes made from MnO 2 showed that high specific capacitance and rate capability should be obtained in principle.…”
mentioning
confidence: 99%
“…The SEM micrograph of sample in Figure 3a Figure 3b. The crystalline part of MoS 2 consists of polygonal particles which may exhibit lamellar structure as also noted by Ye et al [25]. However, small clusters appear on the surface as shown in Figure 3b.…”
Section: Properties and Characteristics Of Catalystsmentioning
confidence: 71%